PVP / UiO-66 composite carbonized material, preparation method and application of PVP / UiO-66 composite carbonized material as MALDI (matrix-assisted laser desorption ionization) matrix in small molecule substance detection

By adding PVP during UiO-66 synthesis and carbonizing at high temperature, PVP/UiO-66 composite carbonized material was prepared, which solved the problems of uncontrollable morphology and size, anisotropy and high laser energy requirements of MOFs in mass spectrometry analysis. , achieving improved accuracy and repeatability of MALDI-MS detection, expanding the analytical species and reducing costs.

CN119284879APending Publication Date: 2025-01-10CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500335.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Metal organic frame materials (MOFs) have problems with uncontrollable morphology and size, anisotropy and high laser energy requirements in mass spectrometry analysis, which affects their accuracy and reproducibility in MALDI-MS detection.

Method used

Using the preparation method of PVP/UiO-66 composite carbonized material, by adding PVP to the UiO-66 synthesis process and carbonizing at high temperature, C-H-PVP-U66 composite carbonized material with regular octahedral structure and excellent chemical stability is formed , as the matrix of MALDI-MS.

Benefits of technology

Improves the accuracy and repeatability of MALDI-MS analysis, reduces laser energy requirements, reduces background noise, expands the types of detection analytes, simplifies the operation process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284879A_ABST
    Figure CN119284879A_ABST
Patent Text Reader

Abstract

The invention discloses a PVP / UiO-66 composite carbonized material, a preparation method and application of the PVP / UiO-66 composite carbonized material as an MALDI (matrix-assisted laser desorption ionization) matrix in small molecule substance detection. The preparation method comprises the following steps: by taking terephthalic acid (H2BDC) and zirconium tetrachloride (ZrCl4) as raw materials, adding polyvinylpyrrolidone (PVP) in the process of synthesizing UiO-66, and then performing high-temperature carbonization on the UiO-66 doped with the PVP, thereby obtaining the PVP / UiO-66 composite carbonized material. The carbonized C-H-PVP-U66-600 material shows excellent desorption ionization performance, and the demand threshold value of laser energy is reduced, so that the damage to an analytical instrument and molecules to be detected is reduced. Meanwhile, the composite carbonized material has a cleaner background peak, the detection sensitivity of small molecule analytes is effectively improved, and the types of detectable analytes are expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of mass spectrometry detection, and in particular to a PVP / UiO-66 composite carbonized material, a preparation method and an application of the composite carbonized material as a MALDI matrix in the detection of small molecule substances. Background Art

[0002] Matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) is a new type of soft ionization biological mass spectrometry technology developed in recent years. Its core lies in finding a suitable matrix to analyze specific substances. In MALDI-MS, commonly used matrices are small organic molecules, such as 2,5-dihydroxybenzoic acid (DHB) or α-cyano-4-hydroxycinnamic acid (CHCA), which are widely used in the analysis of high-mass region analytes (m / z>500 Da). However, these matrices will produce strong bulk peak signals in the low-mass region (m / z<500 Da), which usually affects the accuracy of MALDI-MS in the determination of small mass molecules. In addition, it is sometimes difficult to obtain uniform co-crystallized samples using traditional organic matrices, resulting in poor signal detection.

[0003] To overcome these limitations, researchers have begun to explore new matrix materials, such as carbon-based, silicon-based, and metal / metal oxide materials, to improve the detection efficiency of small molecule analytes. Among these new materials, metal organic framework materials (MOFs) have attracted much attention due to their unique properties such as large specific surface area, high porosity, and adjustable pore size. The high porosity and large specific surface area of ​​MOFs are conducive to forming a uniform co-crystallization system with the analyte; its strong absorption ability in the ultraviolet region meets the requirements of laser energy absorption and transfer of MALDI; and its easy functionalization greatly expands its application range in the detection of small molecule analytes. Nevertheless, the uncontrollable morphology and size of MOFs affect its reproducibility in mass spectrometry analysis; the anisotropy is significant, and the properties of different MOF particles may vary, which is not conducive to standardization and batch application; some MOF materials require higher laser energy to achieve effective desorption ionization in MALDI-MS detection, which may cause damage to the analyte and the instrument. These shortcomings often become challenges in its practical application and require further research and improvement.

[0004] Therefore, it is particularly important to use new synthetic strategies to optimize the structure and properties of MOFs and develop more excellent and efficient MOFs matrices to fully tap the potential of MOFs in mass spectrometry analysis. Summary of the invention

[0005] In response to the technical challenges faced by metal organic framework materials in laser desorption ionization mass spectrometry applications, this paper proposes an innovative MOFs material solution - PVP / UiO-66 composite carbonized material. This new material aims to solve the problems of MOFs in morphology and size control, anisotropy, and high laser energy requirements. This paper will comprehensively explain the preparation method of PVP / UiO-66 composite carbonized material and explore its potential application as a MALDI matrix in small molecule detection. The introduction of this new material is expected to significantly improve the accuracy, repeatability and detection efficiency of MALDI-MS analysis, while simplifying the operating process and reducing costs, opening up a new path for the development of mass spectrometry technology.

[0006] In order to achieve the above-mentioned object and other related objects, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a PVP / UiO-66 composite carbonized material, comprising the following steps: (1) Dissolve terephthalic acid (H2BDC), triethylamine (TEA) and polyvinylpyrrolidone (PVP) in dimethylformamide (DMF) solvent, stir evenly at room temperature, and then add a certain amount of acetic acid; (2) The obtained mixed solution is heated to 120-130 °C in an oil bath, and zirconium tetrachloride (ZrCl4) in DMF solvent is added, and the reaction is carried out at this temperature without stirring for 6-12 h; (3) After the solution is cooled to room temperature, the product is washed and centrifuged to obtain pure H-PVP-UiO-66; (4) In a N2 atmosphere, H-PVP-UiO-66 is carbonized at 500-800°C for a period of time to obtain CH-PVP-U66, i.e., the PVP / UiO-66 composite carbonized material.

[0007] Preferably, the molar ratio of H2BDC, ZrCl4 and PVP is 1:1:(0.005-0.01); More preferably, the molar ratio of H2BDC, ZrCl4 and PVP is 1:1:(0.005-0.085).

[0008] Preferably, the average molecular weight of PVP is between 50,000 and 60,000; More preferably, the average molecular weight of PVP is 55,000.

[0009] Preferably, the usage ratio of H2BDC, TEA and acetic acid is 0.6 mol: 1 mol: 20-21 L.

[0010] In step (1), H2BDC and TEA are first dissolved in DMF solvent respectively, then the two are mixed with PVP, and then a certain amount of DMF solvent is added.

[0011] In step (1), the stirring time at room temperature is 10-15 min.

[0012] In step (2), the reaction time is preferably 10 h.

[0013] In step (3), the product is washed with DMF, acetone, methanol, ethanol and water in sequence.

[0014] In step (4), the temperature of high temperature carbonization is preferably 600-800°C, more preferably 600°C.

[0015] In step (4), the high temperature carbonization time is preferably 6 h.

[0016] In the process of synthesizing UiO-66, PVP is added. Since PVP has the characteristics of a stabilizer and a capping agent, the prepared H-PVP-UiO-66 has a more regular octahedral structure and a more uniform size. Then, it is carbonized at high temperature to become a carbonized MOF material (i.e., CH-PVP-U66), which not only retains a part of the pore structure and structural characteristics of the original MOF, but also has better chemical stability than conventional carbon-based materials, and is not easy to generate carbon cluster ions to damage the ion detection of the analyte.

[0017] Before carbonization, H-PVP-UiO-66 has no matrix effect, but the CH-PVP-U66 composite carbonized material after carbonization has excellent desorption and ionization characteristics. When used as a matrix to analyze analytes, it has the advantages of low laser energy threshold and high desorption and ionization efficiency. The lower laser energy can also increase the detector life, making it an excellent matrix for MALDI-MS.

[0018] The second aspect of the present invention provides a PVP / UiO-66 composite carbonized material prepared by the aforementioned method. The PVP / UiO-66 composite carbonized material has the advantages of both carbon-based materials and MOFs—stable and not easy to produce carbon cluster ions. The background peak of this composite carbonized material is cleaner, which greatly facilitates the detection of analytes in the low mass range.

[0019] The third aspect of the present invention provides a PVP / UiO-66 composite carbonized material prepared by the aforementioned method as a matrix for use in the fields of mass spectrometry imaging, metabolomics, etc., especially as a MALDI-MS matrix in the detection of small molecule metabolites.

[0020] Furthermore, the PVP / UiO-66 composite carbonized material can be used to detect at least one of alanine, glycine, proline, valine, fructose, glucose, maltose, sucrose, serine, tyrosine, aspartic acid, threonine, lysine, glutamic acid, tryptophan, cysteine, isoleucine, leucine, phenylalanine, glutamine, aspartic acid, and histidine.

[0021] As described above, the PVP / UiO-66 composite carbonized material, preparation method and application as MALDI matrix in the detection of small molecule substances of the present invention have the following beneficial effects: 1. In the present invention, PVP is added during the synthesis of UiO-66, and the PVP-doped H-PVP-UiO-66 is carbonized at high temperature. PVP plays a very important role in the composite material. On the one hand, the PVP / UiO-66 composite carbonized material has a more uniform and regular octahedral structure, and has better chemical stability than conventional carbon-based materials, and is not easy to produce carbon cluster ions; on the other hand, the carbonized CH-PVP-U66-600 has efficient desorption and ionization ability and low laser threshold requirement, avoiding damage to the instrument and the molecules to be measured; on the third hand, the composite carbonized material also has a cleaner background peak, which is very helpful for detecting small molecule analytes in the low mass range, greatly expanding the types of detected analytes.

[0022] 2. The preparation method of the PVP / UiO-66 composite carbonized material in the present invention is simple to operate, low in cost, safe and pollution-free, and the prepared PVP / UiO-66 composite carbonized material has uniform particle size, regular morphology, stable structure and properties, and has broad application value in the field of analysis and detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a process flow chart for preparing PVP / UiO-66 composite carbonized material in Example 1 of the present invention.

[0024] Figure 2 These are the SEM and TEM images of the PVP / UiO-66 composite carbonized material prepared in Example 1 of the present invention.

[0025] Figure 3 3A and 3B are thermogravimetric analysis curves of H-PVP-UiO-66 and UiO-66 prepared in Example 1 of the present invention.

[0026] Figure 4 XRD patterns of CH-PVP-U66-600, H-PVP-UiO-66, and UiO-66.

[0027] Figure 5Infrared spectra of CH-PVP-U66-600, H-PVP-UiO-66, and UiO-66.

[0028] Figure 6 This is the mass spectrum of histidine analyzed using H-PVP-UiO-66 as a matrix under carbonization at 500℃, 600℃, 700℃, and 800℃; the histidine concentration is 0.001 mol / L.

[0029] Figure 7 This is a comparison chart of CH-PVP-U66-600 matrix and CHCA, DHB in the analysis of glucose and glycine; where M is the corresponding analyte, and the analyte concentration is 0.01 mol / L.

[0030] Figure 8 This is a comparison of the laser energy used for the analysis of glucose and glycine using CH-PVP-U66-600 matrix, DHB, and CHCA; where M is the corresponding analyte, and the analyte concentration is 0.01 mol / L.

[0031] Fig. 9 This is the mass spectrum of alanine, glycine, proline, valine, fructose, glucose, maltose, and sucrose analyzed using CH-PVP-U66-600 as the matrix; M is the corresponding analyte, M1 is the monosaccharide product formed by the decomposition of sucrose, and the concentration of the analytes is 0.01 mol / L.

[0032] Fig.10 The mass spectra of 18 essential amino acids for the human body were analyzed using CH-PVP-U66-600 as the matrix; the 18 essential amino acids for the human body are alanine, glycine, proline, valine, serine, tyrosine, aspartic acid, threonine, lysine, glutamic acid, tryptophan, cysteine, isoleucine, leucine, phenylalanine, glutamine, aspartic acid, and histidine; among which, the amino acid concentration is 0.01 mol / L. DETAILED DESCRIPTION

[0033] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Example 1

[0034] A PVP / UiO-66 composite carbonized material is prepared by the following method. The preparation process is referenced to Figure 1 : (1) Dissolve 0.6 mmol of H2BDC in 50 mL of DMF solvent and add it to a round-bottom flask. Then add 1 mL of TEA in DMF solution (final concentration is 1 mol / L) and 2.8 g (0.051 mmol) of PVP (average molecular weight is 55000). Then add 90 mL of DMF solvent, stir at room temperature for 10 min, and then add 20.625 mL of acetic acid. (2) Heat the obtained mixed solution to 120 °C in an oil bath, add 10 mL of DMF solution containing 0.6 mmol ZrCl4, and react at this temperature without stirring for 10 h; (3) After the solution was cooled to room temperature, the product was washed with DMF, acetone, methanol, ethanol, and water in sequence, and then centrifuged and vacuumed to obtain 204 mg of pure H-PVP-UiO-66 with a yield of 85%; (4) Under N2 atmosphere, H-PVP-UiO-66 was carbonized at 600°C for 6 h to obtain CH-PVP-U66-600, i.e., the PVP / UiO-66 composite carbonized material. Example 2

[0035] A PVP / UiO-66 composite carbonized material is prepared by the following method: (1) The preparation method of H-PVP-UiO-66 is the same as that of Example 1; (2) Under N2 atmosphere, H-PVP-UiO-66 was carbonized at 500 °C for 6 h to obtain CH-PVP-U66-500. Example 3

[0036] A PVP / UiO-66 composite carbonized material is prepared by the following method: (1) The preparation method of H-PVP-UiO-66 is the same as that of Example 1; (2) Under N2 atmosphere, H-PVP-UiO-66 was carbonized at 700 °C for 6 h to obtain CH-PVP-U66-700. Example 4

[0037] A PVP / UiO-66 composite carbonized material is prepared by the following method: (1) The preparation method of H-PVP-UiO-66 is the same as that of Example 1; (2) Under N2 atmosphere, H-PVP-UiO-66 was carbonized at 800 °C for 6 h to obtain CH-PVP-U66-800. Example 5

[0038] The PVP / UiO-66 composite carbonized material was prepared by the method of Reference Example 1, except that the amount of PVP added was 1.4 g (0.025 mmol). In this example, 192 mg of pure H-PVP-UiO-66 was prepared with a yield of 80%; high-temperature carbonization was performed at 600°C for 6 h. Example 6

[0039] The PVP / UiO-66 composite carbonized material was prepared by the method of Reference Example 1, except that the amount of PVP added was 0.7 g (0.013 mmol). In this example, 180 mg of pure H-PVP-UiO-66 was prepared with a yield of 75%; high temperature carbonization was performed at 600°C for 6h. Example 7

[0040] The PVP / UiO-66 composite carbonized material was prepared by the method of Reference Example 1, except that the amount of PVP added was 0.35 g (0.006 mmol). In this example, 144 mg of pure H-PVP-UiO-66 was prepared with a yield of 60%; high-temperature carbonization was performed at 600°C for 6h. Example 8

[0041] The PVP / UiO-66 composite carbonized material was prepared by the method of Reference Example 1, except that the amount of PVP added was 0.175 g (0.003 mmol). In this example, 120 mg of pure H-PVP-UiO-66 was prepared with a yield of 50%; high-temperature carbonization was performed at 600 °C for 6 h. Example 9

[0042] UiO-66 was prepared by the following method: (1) Dissolve 0.6 mmol of H2BDC in 50 mL of DMF solvent and add it to a round-bottom flask. Then add 1 mL of TEA in DMF solution (final concentration is 1 mol / L), then add 90 mL of DMF solvent, stir at room temperature for 10 min, and then add 20.625 mL of acetic acid; (2) Heat the obtained mixed solution to 120 °C in an oil bath, add 10 mL of DMF solution containing 0.6 mmol ZrCl4, and react at this temperature without stirring for 10 h; (3) After the solution is cooled to room temperature, the product is washed with DMF, acetone, methanol, ethanol, and water in sequence, and then centrifuged and vacuumed to obtain UiO-66.

[0043] Performance Characterization 1. Take SEM and TEM images of CH-PVP-U66-600 prepared in Example 1. Figure 2As shown, it can be seen that the CH-PVP-U66-600 prepared in the present invention has a regular octahedral structure, a uniform particle size, and retains a certain pore structure.

[0044] 2. The H-PVP-UiO-66 prepared in Example 1 and ordinary UiO-66 were subjected to thermogravimetric analysis. Figure 3 As shown, it can be seen that the H-PVP-UiO-66 curve rises, indicating that H-PVP-UiO-66 is successfully doped with PVP on UiO-66.

[0045] 3. The XRD patterns and infrared spectra of H-PVP-UiO-66, CH-PVP-U66-600 and UiO-66 prepared in Example 1 were analyzed respectively. Figure 4 and Figure 5 As shown, it can be seen that the present invention successfully doped PVP into UiO-66, and the properties of CH-PVP-U66-600 obtained after high-temperature carbonization changed.

[0046] 4. CH-PVP-U66-500, CH-PVP-U66-600, CH-PVP-U66-700, and CH-PVP-U66-800 prepared at different carbonization temperatures were used as matrices. The concentration of the prepared matrix solution was 1.5 mg / mL. The matrix solution and the analyte solution were mixed in equal volumes. The concentration of the analyte histidine was 0.001 mol / L. The results are as follows: Figure 6 As shown. It can be concluded that when the carbonization temperature is selected as 600 ℃, the signal intensity of the analyte histidine (His) is the highest, which proves that when the carbonization temperature is selected as 600 ℃, its laser desorption ionization ability as a matrix is ​​the best, and the effect of analyzing the analyte is the best.

[0047] 5. Glucose and glycine were analyzed using traditional organic matrix DHB, CHCA and CH-PVP-U66-600 matrix prepared in Example 1, respectively. The test results are as follows: Figure 7 As shown, M is the corresponding analyte, and the analyte concentration is 0.01 mol / L. The concentrations of DHB and CHCA matrix solutions are both 10 mg / mL, and the concentration of CH-PVP-U66-600 matrix solution is 1.5 mg / mL. According to the comparison of the test results, under the same laser energy, CH-PVP-U66-600 has lower background noise and cleaner background peaks, which is also very helpful for detecting small molecule analytes with higher detection accuracy.

[0048] 6. Figure 8This is a comparison of the laser energy used for analyzing glucose and glycine using DHB, CHCA, and CH-PVP-U66-600 matrices. According to the comparison of the test results, CH-PVP-U66-600 only needs 10% of the laser energy to detect glucose, while DHB and CHCA both need to reach 30%. It can be seen that the laser threshold required for the PVP / UiO-66 composite carbonized material prepared by the present invention is much lower than that of most nanomaterials and organic matrices, so the life of the detector can be increased, extending the service life of the instrument.

[0049] 7. Fig. 9 Using CH-PVP-U66-600 as the matrix, the mass spectra of alanine, glycine, proline, valine, fructose, glucose, maltose, and sucrose were analyzed respectively; where M is the corresponding analyte, M1 is the monosaccharide formed by the decomposition of sucrose, and the concentration of the analytes is 0.01 mol / L.

[0050] 8. Fig.10 CH-PVP-U66-600 was used as the matrix to analyze 18 essential amino acids for the human body; the 18 essential amino acids for the human body are alanine, glycine, proline, valine, serine, tyrosine, aspartic acid, threonine, lysine, glutamic acid, tryptophan, cysteine, isoleucine, leucine, phenylalanine, glutamine, aspartic acid, and histidine; among which, the amino acid concentration is 0.01 mol / L.

[0051] according to Fig. 9 and Fig.10 The test results show that the PVP / UiO-66 composite carbonized material prepared by the present invention expands the types of detected analytes. Compared with traditional organic matrices, the PVP / UiO-66 composite carbonized material detects more types of amino acids, which is helpful for effective application in mass spectrometry imaging, metabolomics and other fields.

[0052] In summary, the present invention uses H2BDC and ZrCl4 as raw materials, adds PVP in the process of synthesizing UiO-66, and then carbonizes the H-PVP-UiO-66 doped with PVP at high temperature to obtain the PVP / UiO-66 composite carbonized material. The doping of PVP plays a very important role, which makes the PVP / UiO-66 composite carbonized material have a more uniform and regular octahedral structure, and has better chemical stability than conventional carbon-based materials, and is not easy to produce carbon cluster ions to damage the ion detection of the analyte; the CH-PVP-U66-600 after carbonization has a high desorption ionization efficiency and a low laser threshold requirement, avoiding damage to the instrument and the molecules to be measured; in addition, the composite carbonized material has a cleaner background peak in the low-quality region, which is helpful for the detection of small molecule analytes and expands the types of detected analytes. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.

[0053] The above embodiments are merely illustrative and not intended to limit the present invention. All equivalent modifications or changes made by those skilled in the art without departing from the spirit and technical concept disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A PVP / UiO-66 composite carbonized material, characterized in that: The PVP / UiO-66 composite carbonized material is obtained by high-temperature carbonization of UiO-66 (Zr) doped with PVP; the high-temperature carbonization temperature is 500-800°C.

2. The PVP / UiO-66 composite carbonized material according to claim 1, characterized in that: The PVP and Zr in UiO-66(Zr) 4+ The molar ratio is (0.005-0.1):

1.

3. The PVP / UiO-66 composite carbonized material according to claim 1, characterized in that: The average molecular weight of the PVP is between 50,000 and 60,000.

4. The PVP / UiO-66 composite carbonized material according to claim 1, characterized in that: The high temperature carbonization time is 6 hours.

5. The method for preparing the PVP / UiO-66 composite carbonized material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving terephthalic acid (H2BDC), triethylamine (TEA) and polyvinylpyrrolidone (PVP) in dimethylformamide (DMF) solvent, stirring evenly at room temperature, and then adding acetic acid to obtain a mixed solution; (2) Heat the obtained mixed solution to 120-130 °C in an oil bath, add a DMF solution of zirconium tetrachloride (ZrCl4), and allow to react for 6-12 h; (3) After the solution is cooled to room temperature, the product is washed and centrifuged to obtain H-PVP-UiO-66; (4) In a N2 atmosphere, the H-PVP-UiO-66 is carbonized at a high temperature of 500-800°C to obtain the PVP / UiO-66 composite carbonized material.

6. The method for preparing the PVP / UiO-66 composite carbonized material according to claim 5, characterized in that: The molar ratio of H2BDC, ZrCl4 and PVP is 1:1:(0.005-0.1).

7. The method for preparing the PVP / UiO-66 composite carbonized material according to claim 5, characterized in that: The usage ratio of H2BDC, TEA and acetic acid is 0.6 mol: 1 mol: 20-21 L.

8. The method for preparing the PVP / UiO-66 composite carbonized material according to claim 5, characterized in that: In step (1), H2BDC and TEA are first dissolved in DMF solvent respectively, then the two are mixed with PVP, and then a certain amount of DMF solvent is added.

9. Use of the PVP / UiO-66 composite carbonized material according to claim 1 as a MALDI-MS matrix in the detection of small molecules.

10. The use according to claim 9, characterized in that: The PVP / UiO-66 composite carbonized material can be used to detect at least one of alanine, glycine, proline, valine, fructose, glucose, maltose, sucrose, serine, tyrosine, aspartic acid, threonine, lysine, glutamic acid, tryptophan, cysteine, isoleucine, leucine, phenylalanine, glutamine, aspartic acid, and histidine.